2016
DOI: 10.1186/s12887-016-0735-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of spontaneous closure of isolated ventricular septal defects in utero and postnatal life

Abstract: BackgroundVentricular septal defect (VSD) is a highly prevalent fetal congenital heart defect, which can become spontaneously closed during infancy. The current study aims to characterize fetal VSDs that were subsequently spontaneously closed in the first 2 years of life in eastern China.MethodsBetween January 2011 and December 2013, 257 fetal patients diagnosed with isolated VSD by fetal echocardiography at Nanjing Maternity and Child Health Care Hospital, China, were enrolled in the study. Subjects were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 44 publications
2
15
0
3
Order By: Relevance
“…Membranous VSDs close by adherence of tricuspid valve leaflets, creating an aneurysm that closes the defect [1 , 7 , 8] . It has been suggested that the spontaneous closure of muscular VSDs could be due to muscular encroachment of the septal defect along with superimposed fibrosis or by fibrous tissue formation around the margins leading to apposition of the edges of the defect [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Membranous VSDs close by adherence of tricuspid valve leaflets, creating an aneurysm that closes the defect [1 , 7 , 8] . It has been suggested that the spontaneous closure of muscular VSDs could be due to muscular encroachment of the septal defect along with superimposed fibrosis or by fibrous tissue formation around the margins leading to apposition of the edges of the defect [9] .…”
Section: Discussionmentioning
confidence: 99%
“…With regards to SC of VSD, Li et al (2016) reported the frequency of cases in which VSD was diagnosed during the fetal period, and SC was confirmed within the first 2 years of life. According to this report, SC occurred in 42.8% of patients during gestation and within the first 2 years of life; birth weight and defect meter showed significant differences between the three groups (SC during gestation, SC after birth, and persistent VSD).…”
Section: Discussionmentioning
confidence: 99%
“…P‐VSD closure was thought to occur as a result of damage caused by a high‐velocity jet to damage the endothelium at the edge of the VSD or the septal leaflet of the tricuspid valve, both of which can lead to accumulation of platelets and production of fibrous tissue . On the other hand, the spontaneous closure of m‐VSD was due to muscular encroachment of the septal defect along with superimposed fibrosis or fibrous tissue formation around the margins leading to apposition of the edges of the defect . Another reason may be that m‐VSD size was slightly smaller than p‐VSD.…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular septal defect (VSD) is the most common congenital heart disease (CHD), accounting for almost 50% of all CHD . The estimated prevalence of VSD is 2 to 3.94 per 1000 live births diagnosed by echocardiography . Two‐dimensional (2D) combined color Doppler echocardiography makes it easy to diagnose VSD, and to measure size and position of defect, as well as to evaluate the anatomical relationship with the surrounding tissue.…”
Section: Introductionmentioning
confidence: 99%